2020
DOI: 10.1002/acm2.12904
|View full text |Cite
|
Sign up to set email alerts
|

Investigating split‐filter dual‐energy CT for improving liver tumor visibility for radiation therapy

Abstract: Accurate liver tumor delineation is crucial for radiation therapy, but liver tumor volumes are difficult to visualize with conventional single-energy CT. This work investigates the use of split-filter dual-energy CT (DECT) for liver tumor visibility by quantifying contrast and contrast-to-noise ratio (CNR). Methods: Split-filter DECT contrast-enhanced scans of 20 liver tumors including cholangiocarcinomas, hepatocellular carcinomas, and liver metastases were acquired. Analysis was performed on the arterial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A limited number of studies investigate the clinical value of DECT-based delineations. A PubMed database search with the criteria “DECT 1 ” and “RT 1 “ and “delineation” resulted in only 12 publications, which mainly focused on optimal DECT recons in terms of maximum contrast or signal-to-noise ratios (CNR/SNR) or MAR considerations [12] , [18] , [19] , [20] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] . Tumors and OARs in the brain, HN, lung, liver and pancreas were investigated, and in general VMI < 60 keV had favorable CNR as compared to 120 kV SECT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies investigate the clinical value of DECT-based delineations. A PubMed database search with the criteria “DECT 1 ” and “RT 1 “ and “delineation” resulted in only 12 publications, which mainly focused on optimal DECT recons in terms of maximum contrast or signal-to-noise ratios (CNR/SNR) or MAR considerations [12] , [18] , [19] , [20] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] . Tumors and OARs in the brain, HN, lung, liver and pancreas were investigated, and in general VMI < 60 keV had favorable CNR as compared to 120 kV SECT.…”
Section: Discussionmentioning
confidence: 99%
“…Different source-based DECT acquisitions exist such as performing two helical scans at two different energies (typically at 80 and 140 kV) [5] , two orthogonal sources simultaneously operating at different energies [6] , rapid (<0.5 ms) kV switching of a single source [7] , [8] , and splitting a single-source beam longitudinally using filtration [4] , [9] . The latter technique [10] , [11] , [12] , here termed TwinBeam (TB), is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that VMI 40keV exhibits the highest contrast-to-noise ratio, which is advantageous for lesion detection. VMI 40keV maximizes the contrast of liver tumors, improves the image quality of multiphase abdominal enhancement scans, and enhances the detection of liver and pancreatic lacerations [ 13 , 14 ]. However, DECT is more expensive than conventional CT, which limits its widespread adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Combining kV-CT images with MV-CT images potentially can achieve dual-energy imaging. A number of studies have reported that utilizing features from dual-energy imaging can improve tumor recognition (Çamlıdağ et al 2019, DiMaso et al 2020, Shen et al 2021. However, the corresponding kV-CT images of the online MV-CT images are not available during each fraction of tomotherapy.…”
Section: Introductionmentioning
confidence: 99%